The Effect of Reduce Salinity on Behavior and Stress Response in Vannamei Shrimp (Litopenaeus vannamei) - Rum, Edita; Jasmanindar, Yudiana; Lukas, Ade Yulita Hesti (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
One of the parameters that play an important role in the success of vannamei shrimp cultivation is salinity. This study aims to determine the effect of decreasing salinity on the behavior and stress response of vannamei shrimp. The test animals used were vannamei shrimp, which were in logs with an average weight of 4.6 – 6.3g. This study used a completely randomized design (CRD) with different salinity reduction treatments in each maintenance medium, namely Treatment A without decreasing salinity, Treatment B decreasing salinity 2 ppt per 6 hours for 24 hours, Treatment C decreasing salinity 2 ppt per 4 hours for 24 hours, Treatment D decreased salinity 2 ppt per 2 hours for 24 hours, each treatment was repeated 3 times. Blood glucose was measured after the decrease in salinity and on the last day of the study. Blood glucose collection was carried out at the fifth swimming leg on white shrimp using a 1 ml syringe that had been rinsed using Na Citrate with the aim that the blood glucose taken did not clot quickly. The results showed a decrease in salinity caused by shrimp stress. The concentration of vannamei shrimp blood glucose increased (13.66 – 52.37mg/dl). Treatment D was the best glucose concentration to suppress blood glucose concentrations (13.66mg/dl). Based on the data analysis of blood glucose concentration (p<0.05) it continued with the real difference test. Vannamei shrimp behavior during salinity reduction showed a response that was not different from all treatments. Salinity 6 ppt is good salinity in the process of suppressing blood glucose concentrations when changes in water salinity occur.